2018
DOI: 10.1016/j.bbadis.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular histones activate autophagy and apoptosis via mTOR signaling in human endothelial cells

Abstract: Circulating histones have been proposed as targets for therapy in sepsis and hyperinflammatory symptoms. However, the proposed strategies have failed in clinical trials. Although different mechanisms for histone-related cytotoxicity are being explored, those mediated by circulating histones are not fully understood. Extracellular histones induce endothelial cell death, thereby contributing to the pathogenesis of complex diseases such as sepsis and septic shock. Therefore, the comprehension of cellular response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 66 publications
2
50
0
Order By: Relevance
“…Histones also interact with Toll-like receptors (TLRs) and proin ammatory cytokine/chemokine, released through MyD88, NFκB, and NLRP3 in ammasomedependent pathways [17,21]. In previous studies, extracellular histone-treated HUVECs decreased eNOS expression [39], suppressed the Akt signaling pathway [15], and eventually induced apoptosis in a dosedependent manner. In many sepsis animal models, endothelial cell damage is associated with apoptosis [19,40,41].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Histones also interact with Toll-like receptors (TLRs) and proin ammatory cytokine/chemokine, released through MyD88, NFκB, and NLRP3 in ammasomedependent pathways [17,21]. In previous studies, extracellular histone-treated HUVECs decreased eNOS expression [39], suppressed the Akt signaling pathway [15], and eventually induced apoptosis in a dosedependent manner. In many sepsis animal models, endothelial cell damage is associated with apoptosis [19,40,41].…”
Section: Discussionmentioning
confidence: 97%
“…In humans, increased levels of circulating histones have also been recognized in septic and ARDS patients depending on their severity [34,35]. Recently, some studies have shown that extracellular histones are cytotoxic toward the endothelium in vitro [15] and cause lethal intra-alveolar hemorrhage in mice [21][22][23]36]. Therefore, extracellular histone is increasingly becoming of concern and examined as a therapeutic target for sepsis and ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations